Bioactive antiinflammatory antibacterial hemostatic citrate-based dressing with macrophage polarization regulation for accelerating wound healing and hair follicle neogenesis - Wenguang Liu; Min Wang; Wei Cheng; Wen Niu; Mi Chen; Meng Luo; Chenxi Xie; Tongtong Leng; Long Zhang; Bo Lei (Bioactive Materials, 2021)
The efficient cutaneous wound healing accompanied with the enhanced skin appendage regeneration is still a challenge. The bacterial infection and excessive/prolonged inflammation inhibit wound healing process and result in the scar formation. Herein, we reported an anti-inflammatory polycitrate-polyethyleneimine-Ibuprofen (PCEI) and multifunctional PCEI-based F127-ε-polypeptide-alginic (FEA) dressing (FEA-PCEI) for accelerating wound healing and hair follicle neogenesis. PCEI showed the excellent anti-inflammation function through stimulating macrophage towards anti-inflammatory M2 subtype polarization. The FEA-PCEI dressing showed the temperature-response gelation, injectability, robust antibacterial activity, light-damage-resistant, homeostasis ability, and good cytocompatibility. The optimized dosage of FEA-PCEI dressing could significantly accelerate wound healing with anti-infection ability, reduce the scar formation, and promote the hair follicle neogenesis. This study provided a wound-repairing strategy through regulating the phenotype of immune cells by the designing bioactive multifunctional biomaterials.